EXAMINATION 8TH GRADE STUDENTS’ COGNITIVE STRUCTURES ABOUT PHYSICAL AND CHEMICAL CHANGES THROUGH WORD ASSOCIATION TEST - NAKİBOGLU, Canan (The Eurasia Proceedings of Educational and Social Sciences, 2017)
In this study it is aimed to investigate middle school students’ cognitive structures of physical and chemical changes through word association test (WAT). The data were collected from 126 eight grade students. The WAT was used as data a data collection instrument developed by the researcher in her previous study. At the beginning of the study, the physical and chemical change topic placed in the middle school science curriculum was examined and also the opinions of the two science teachers were asked to establish the content validity of the stimulus words of WAT. The same WAT comprised of eight total stimulus words was decided to use without modification. The response frequency mapping method was used to examine students’ cognitive structure which was developed by the researcher. At the end of the study, it was found that all stimulus words appeared and were added to the map at the frequency range 16≤f≤20 as five separate islands. Besides, it was concluded that the eight grade students, like ninth and tenth grade students, could not associate with the concept of energy with other concepts of the subject.